Enhancing Service Encounter Proficiency through Structured Input and Output in Tourism Education - Hasrul Hasrul; Muhammad Arfin Muhammad Salim; Uyunnasirah Hambali; Faradillah Saputri (Newinera Publisher, 2026)
This research investigates the persistent gap between theoretical English instruction and the practical demands of the global tourism industry. While travelers rely on seamless communication to steer various service encounters students often struggle with a profound lack of confidence and linguistic passivity that hinders their professional growth. We implemented a structured input and output framework based on the presentation and practice and production sequence to determine its impact on the communicative effectiveness of sixty vocational learners. Our quantitative analysis utilized pre-test and post-test performance metrics to measure oral fluency and linguistic accuracy and pragmatic competence across two distinct groups. The data reveals that the experimental group achieved statistically significant gains in all domains with a speech rate reaching over one hundred syllables per minute and an accuracy ratio of seventy seven percent. These results prove that intentional instructional sequencing acts as a vital bridge for preparing industry ready professionals who can respond spontaneously in high stakes travel scenarios. This study provides a replicable roadmap for vocational institutions seeking to transform English from a passive subject into a dynamic asset for international service excellence.